1998
DOI: 10.3354/meps166247
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetric distribution and movements of red mullet Mullus surmuletus

Abstract: Using data from bottom-trawl surveys conducted each summer, winter and spring on the Cretan shelf from 1988 to 1991, we examined the bathymetric distribution of red mullet Mullus surmuletus. Additionally, we used data from 3 yr (1991 to 1993) of monthly sampling in the Iraklion Gulf.Depth, temperature and salinity data were combined with biological data on abundance, biomass, fish size, age, sex and maturity. The ranges of bottom depth, temperature and salinity over which red mullet is distributed were establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 16 publications
1
39
1
2
Order By: Relevance
“…Bathymetric distribution according to demersal fish size has been already reported (Lukens, 1981;MacPherson and Duarte, 1991). The relationships, examined in our study, showed a general trend going towards a greater size with increasing depth, which was also reported in other studies (Rooker, 1995;Machias et al, 1998;Rex and Etter, 1998). However, the depth-body size relationship was weaker at intermediate depths due to a spatial overlap.…”
Section: Discussionsupporting
confidence: 27%
“…Bathymetric distribution according to demersal fish size has been already reported (Lukens, 1981;MacPherson and Duarte, 1991). The relationships, examined in our study, showed a general trend going towards a greater size with increasing depth, which was also reported in other studies (Rooker, 1995;Machias et al, 1998;Rex and Etter, 1998). However, the depth-body size relationship was weaker at intermediate depths due to a spatial overlap.…”
Section: Discussionsupporting
confidence: 27%
“…Thus, in Basque waters, S. solea is targeted with trammel nets in deeper waters in autumn-winter and in shallower waters in spring-summer. Finally, Mullus surmuletus and Pagellus erythrinus are both characterised by a spring-summer spawning season, with spawners occurring at mid-shelf depths and young individuals on shallow, vegetated bottoms (Machias et al, 1998;Somarakis and Machias, 2002). As a result, they were both caught in spring-summer at greater depths, with Mullus surmuletus mainly with the 40 mm net and Pagellus erythrinus with the 48 and 56 mm nets (based also on the catches for each inner panel mesh size per season; not shown here).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the recruitment for most of the species in the surveyed areas, takes place in shallow water near the coastline (depth < 60 m). Although there is always an overlap of juveniles and adults, the majority of juveniles stay in shallow waters, while adults remain in deep waters after their first maturation, usually in spring (Tsimenides et al 1992, Machias et al 1998, Labropoulou et al 1999, Machias & Labropoulou 2002, Somarakis & Machias 2002. The presence of fish farms could result in a higher degree of habitat separation between juvenile and adults, as well as in an increase in the residence time of juveniles near the coast.…”
Section: Discussionmentioning
confidence: 99%